Dry-season cattle fattening by smallholder farmers in the semi-arid zone of Mali - Bartholomew, P.W.; Ly, R.; Nantoume, H.; Koné, N'G.; Traoré, B.; Khibe, T.; Sissoko, K.; Baur, H. (1992)
Presents results of a study of a beef-fattening project in which smallholder farmers in the semi-arid zone of Mali were provided with credit to purchase mature cattle for fattening programme. The daily weight gain in animals kept permanently housed was on average higher than in animals which were allowed out to graze and only provided with supplementary feed in the stable. The loss in individual animal performance was apparently offset by a saving in labour for forage collection of approximately two hours per day. Animals of the Maure breed gained weight at a significantly higher rate than Peul animals even when both breeds were maintained under apparently similar conditions of management.